The alloy-oxide interfacial ensemble effect of a multilayer core–shell nanomotor for hydrogen generation from ammonia borane. Issue 7 (7th March 2022) - Guan, Shuyan; Guo, Yong; Zhang, Huanhuan; Liu, Xianyun; Fan, Yanping; Liu, Baozhong
Abstract : CoCuO@CoCu–C nanomotor composed of alloyed cores (CoCu) and oxidized shells (CoCuO) was obtained by pyrolysis and oxidation of CoCu precursor. CoCuO@CoCu–C presents the optimal TOF value of 38 min −1 for ammonia borane hydrolysis at 298 K. Abstract : The hydrogen production from ammonia borane (AB) requires cheap and high-efficiency catalysts. Core-shell and alloy nanostructures have gained considerable attention due to new physicochemical properties and high catalytic activity. Herein, a CoCuO@CoCu–C nanomotor composed of alloyed cores (CoCu) and oxidized shells (CoCuO) was obtained by pyrolysis and oxidation of the CoCu precursor. CoCuO@CoCu–C presents an optimal TOF value of 38 min −1 for ammonia borane hydrolysis at 298 K and no dramatic deterioration during the stability test. The CoCuO@CoCu–C nanomotor with a multilayer core–shell nanostructure that contains a CoCu bimetallic core responsible for magnetic transmission, a partially oxidized CoCuO shell for promoting particle transport, and a thin carbon layer for stabilizing. Further characterization studies and density functional theory (DFT) simulations present that the superior AB hydrolysis performance of the core–shell CoCuO@CoCu–C nanomotor might originate from abundant active sites and reduction of the catalytic activation energy. The alloy core of CoCu and the shell of CoCuO as the active site display a positive effect in promoting the adsorption and dissociation of AB and H2 O molecules, respectively. This research provides an attractive strategy for rational design of transition metal core–shell structured catalysts in energy-related heterogeneous catalysis.